Secondary membranous nephropathy in a patient with myasthenia gravis without thymic disease, and partial remission induced by adrenocorticotropic hormone therapy. (August 2019) - Hanna, Ramy M; Arman, Farid; Selamet, Umut; Wallace, William D; Barsoum, Marina; Rastogi, Anjay; Nobakht, Niloofar; Shieh, Perry
Membranous glomerulonephritis is the most common glomerular disease in adults. Its primary form has been characterized with formation of phospholipase A2 receptor antibodies. Malignancy, infections, and autoimmune disorders are the most common causes of secondary membranous glomerulonephritis. We present a case of a 55-year-old African American female who presented with nephrotic range proteinuria and diagnosed with secondary membranous glomerulonephritis based on distinct pathological features on kidney biopsy and absence of serum phospholipase A2 receptor antibodies. She initially underwent extensive workup for malignancies, infections, and common autoimmune disorders which were all negative. Her proteinuria remained resistant to steroid treatment and she was treated with subcutaneous adrenocorticotropic hormone injections. Meanwhile, she was also diagnosed with the anti-muscle specific kinase antibody variant of myasthenia gravis. In literature, there are few case reports of myasthenia gravis as a cause of secondary membranous glomerulonephritis. In our case, the lack of other inciting factors also suggested this association.